2009
DOI: 10.1111/j.1467-839x.2008.01267.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a moral and benevolent leader: Probing the interactions of the dimensions of paternalistic leadership

Abstract: Paternalistic leadership has three dimensions: authoritarianism, benevolence and morality. Although it is important to understand how these dimensions interact to impact leadership effectiveness, previous studies have failed to identify consistent interaction effects of these dimensions, probably because of the high intercorrelations among the three dimensions. By manipulating the three dimensions independently in an experimental study (N = 265 Taiwanese employees), we found that: (i) benevolence and morality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
89
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 15 publications
(43 reference statements)
5
89
0
1
Order By: Relevance
“…Although some studies find that benevolence positively predicts follower performance (e.g,. Chan & Mak, 2012;Chan, Huang, Snape, & Lam, 2013;Chen et al, 2014Chen et al, , 2015, others maintain that leaders exhibiting high levels of personal concern for followers do not necessarily always result in favorable follower work outcomes (e.g., Niu, Wang, & Cheng, 2009;Pellegrini et al, 2010;Wang, Chiang, Tsai, Lin, & Cheng, 2013;Wu, Huang, Li, & Liu, 2012). Indeed, a leader who is too nice could perhaps unintentionally harm his or her team (Fertik, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies find that benevolence positively predicts follower performance (e.g,. Chan & Mak, 2012;Chan, Huang, Snape, & Lam, 2013;Chen et al, 2014Chen et al, , 2015, others maintain that leaders exhibiting high levels of personal concern for followers do not necessarily always result in favorable follower work outcomes (e.g., Niu, Wang, & Cheng, 2009;Pellegrini et al, 2010;Wang, Chiang, Tsai, Lin, & Cheng, 2013;Wu, Huang, Li, & Liu, 2012). Indeed, a leader who is too nice could perhaps unintentionally harm his or her team (Fertik, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Chan et al () reported that the negative effect of authoritarianism on task performance and citizenship behavior was weakened by its interaction with benevolence. However, the AL by BL interaction effects on employee outcomes have proven elusive (Chan et al, ; Chen et al, ; Cheng, Chou, Wu, Huang, & Farh, ; Cheng et al, ; Farh, Cheng, Chou, & Chu, ; Niu, Wang, & Cheng, ).…”
Section: Introductionmentioning
confidence: 99%
“…Farh and Cheng (2000) state that paternalistic leadership dimensions affect the employees' effectiveness. Niu et al (2009) argue that high benevolence strengths the positive relationship between authorism and subordinates' activities and that the moral virtues of leader will enhance the influence of the leader' authoritarian and benevolence characteristics on the employees' effectiveness. Cheng et al (2004) claim that if the leader has a sense of high benevolence, authoritarianism has either positive effect or no effects but if the leader has a sense of low benevolence, authoritarianism has negative effects on employees' behaviors.…”
Section: Paternalistic Leadershipmentioning
confidence: 99%